Bacterial diversity in primary and secondary/persistent endodontic infections by Checkerboard DNA-DNA Hybridization technique - Endo, Marcos Sergio; Cardoso, Erica Reginato; Pavan, Nair Narumi Orita; de Morais, Carlos Alberto Herrero; Martinho, Frederico Canato [UNESP] (Dental Press International, 2017)
Introduction: One of the main advantages of the molecular diagnostic methods is detecting microorganisms using the bacterial DNA, leading to a more accurate microbial characterization. Objective: This paper aims to study the bacterial diversity present in primary and secondary/ persistent endodontic infections, comparing the profile of the existing microbial communities before and after endodontic therapy. Methods: Microbiological samples were collected using sterile/non-pyrogenic paper points in teeth with primary endodontic infections (n = 10) and teeth with persistent/secondary endodontic infections (n = 10), before (T1) and after endodontic therapy (T2). The presence and levels of 40 bacterial species in endodontic infections were investigated by checkerboard DNA-DNA hybridization. Results: In primary endodontic infections, higher levels of P. micra, F. nucleatum sp. nucleatum, S. constellatus, P. gingivalis, G. morbillorum, P. endodontalis, T. denticola, P. acnes, S. gordonii, S. mitis, V. parvula and C. rectus were found In T1. For T2, the most frequent bacteria were P. micra, S. oralis and P. acnes. The most frequent species found in T1, considering secondary endodontic infections group were: P. acnes, P. micra, S. constellatus, G. morbillorum, C. rectus, A. naeslundii, S. mitis and S. oralis. In T2, the most frequent species were E. faecalis and P. acnes. Conclusion: This study confirmed the distinctness of microbial communities in primary and secondary endodontic infections. Furthermore, clinical endodontic procedures were significantly effective in reducing the prevalence, the detection levels and bacterial diversity.
Keywords: Bacteria; Dental pulp cavity; Endodontics